Rationale and protocol paper for the Healthy Active Peaceful Playgrounds for Youth (HAPPY) study - Wayne Cotton; Dean Dudley; Kirsten Jackson; Matthew Winslade; Janice Atkin (BMC, 2017)
Abstract Background A growing body of evidence suggest an association between physical activity levels and students psychological well-being. A number of research studies have evaluated playground interventions that aim to increase physical activity levels, decrease conflict and bullying, and improve students behaviour. The HAPPY Study will evaluate the success of an intervention combining environmental modifications, teacher development, and peer support that can culminate in an easy to implement, low cost and effective model for increasing physical activity, and improving psychological well-being for children. Methods/Design Data will be collected at six New South Wales (NSW) primary schools, on physical activity levels, on-task time during classes, and social support for physical activity during a 12 month Cluster Controlled Trial (CT). Three quantitative data collection tools will be used to capture student's physical activity levels during lunch and recess breaks (the SOPARC tool), student's on-task behaviour during classes following recess and lunch breaks (the BOSS tool) and where students receive the most encouragement to be physically active from (the Physical Activity Social Support Scale survey). Baseline data will be analysed against follow-up data, collected after an intervention that is rolled out in all schools as part of a stepped wedge CT design. Discussion A review of relevant Australian and New Zealand literature suggests that playground interventions can be successful at increasing physical activity levels, increasing social and conflict resolution skills in students, and decreasing incidences of bullying. This study will investigate any correlation between physical activity levels, and student behaviour during classes following breaks. Trial Registration Australian and New Zealand Clinical Trials Register ACTRN12616000575437 , registered May 2016.